Faktor-faktor yang Mempengaruhi Jumlah Penyerapan Tenaga Kerja Industri Mikro Kecil di Indonesia - Isra Habibi; Joan Marta (Jurnal Kajian Ekonomi dan Pembangunan, 2023)
This study aims to identify and analyze the factors that influence the absorption of micro and small industrial workers in Indonesia. This study uses secondary data sourced from the Indonesian Central Bureau of Statistics with the research variables grouped into two parts, namely the dependent variable which in this study is defined as the absorption of small micro-industrial workers and the independent variables consisting of capital, wage levels and output values. This study uses panel data regression analysis with the selected method, namely the Fixed Effect Model (FEM). The results of the research in the analysis of the micro-industry equation show that capital and wage levels have a positive and significant effect on the absorption of micro-industrial labor in Indonesia, while the output value has a positive and insignificant effect on the absorption of micro-industrial labor in Indonesia. The results of the research in the small industry equation analysis show that capital has a positive and insignificant effect on the absorption of small industry workers in Indonesia, while the wage rate and output value have a positive and significant effect on the absorption of small industry workers in Indonesia.